Detection of vapor-phase organophosphate threats using wearable conformable integrated epidermal and textile wireless biosensor systems - Mishra, Rupesh K.; Martín, Aida; Nakagawa, Tatsuo; Barfidokht, Abbas; Lu, Xialong; Sempionatto, Juliane R.; Lyu, Kay Mengjia; Karajic, Aleksandar; Musameh, Mustafa M.; Kyratzis, Ilias L.; Wang, Joseph (Biosensors & bioelectronics, 2018)
Flexible epidermal tattoo and textile-based electrochemical biosensors have been developed for vapor-phase detection of organophosphorus (OP) nerve agents. These new wearable sensors, based on stretchable organophosphorus hydrolase (OPH) enzyme electrodes, are coupled with a fully integrated conformal flexible electronic interface that offers rapid and selective square-wave voltammetric detection of OP vapor threats and wireless data transmission to a mobile device. The epidermal tattoo and textile sensors display a good reproducibility (with RSD of 2.5% and 4.2%, respectively), along with good discrimination against potential interferences and linearity over the 90–300mg/L range, with a sensitivity of 10.7µA∙cm3∙mg−1 (R2 = 0.983) and detection limit of 12mg/L in terms of OP air density. Stress-enduring inks, used for printing the electrode transducers, ensure resilience against mechanical deformations associated with textile and skin-based on-body sensing operations. Theoretical simulations are used to estimate the OP air density over the sensor surface. These fully integrated wearable wireless tattoo and textile-based nerve-agent vapor biosensor systems offer considerable promise for rapid warning regarding personal exposure to OP nerve-agent vapors in variety of decentralized security applications. Wearable Conformable Integrated Epidermal and Textile Wireless Biosensor Systems for vapor-phase detection of nerve-agent threats. [Display omitted] •Wearable epidermal Tattoo and textile biosensor for OP vapor detection.•Simple method to nebulize OP.•Smallest flexible square wave voltammetry-based electronic board.•Wireless data transmission for wearable electronics.